Near-complete genome sequences of a rice necrosis mosaic virus isolate infecting rice in Argentina - Solís, V.E.; Bangratz, M.; Brugo Carivali, María Florencia; Comte, A.; Luciani, Cecilia Elizabeth; Lacombe, S.; Fontana, Maria Laura; Filloux, D.; Pachecoy, Maria Ines; Fernandez, E.; Dirchwolf, Pamela Maia; Ayala, Jorge Omar Antonio; et al. (American Society for Microbiology, 2026)
While rice necrosis mosaic virus (RNMV) has only been described in Asia, we identified this virus on a rice plant from Argentina using a viral metagenomic approach. We further confirmed this result by RT-PCR and small-RNA Illumina sequencing to obtain the near-complete genome and to confirm actual infection by RNMV.